Causes, Symptoms, Treatment of Symphisit - Isroilova Guljannat Pardabaevna; Abduboqieva Durdona Dilshod qizi; Abduboqiev Madaminbek Zafarovich (Scholars Digest Publishing, 2023)
Symphysitis is a pathology of the bone pelvis, which consists in an increase in the gap of the pubic joint, the development of pain in the symphysis and inflammation in the tissues. Most often, an anomaly appears in the 1st period of gestation, and its severity increases as the birth approaches. It occurs in 50% of pregnant women. In 25% of cases, symphysis dysfunction requires treatment, and in 8% of women, the disease causes a violation of motor activity - temporary disability. In some women, pelvic pain persists after childbirth for 4-6 months.
Keywords: symphysitis, pregnancy, diagnostics, bone pelvis, complications, fetus, disease.